STRUKTUR KOMPLEKS DALAM BAHASA INDONESIA ILMIAH DAN MASALAH PENERJEMAHANNYA KE DALAM BAHASA INGGRIS - Ni Ketut Mirahayuni; Susie Chrismalia Garnida; Mateus Rudi Supsiadji (Universitas 17 Agustus 1945 Surabaya, 2017)
Abstract. Translating complex structures have always been a challenge for a translator since the structures can be densed with ideas and particular logical relations. The purpose of translation is reproducing texts into another language to make them available to wider readerships. Since language is not merely classification of a set of universal and general concept, that each language articulates or organizes the world differently, the concepts in one language can be radically different from another. One issue in translation is the difference among languages, that the wider gaps between the source and target languages may bring greater problems of transfer of message from the source into the target languages (Culler, 1976). Problematic factors involved in translation include meaning, style, proverbs, idioms and others. A number of translation procedures and strategies have been discussed to solve translation problems. This article presents analysis of complex structures in scientific Indonesian, the problems and effects on translation into English. The study involves data taken from two research article papers in Indonesian to be translated into English. The results of the analysis show seven (7) problems of Indonesian complex structures, whose effect on translation process can be grouped into two: complex structures related to grammar (including: complex structure with incomplete information, run-on sentences, redundancy , sentence elements with inequal semantic relation, and logical relation and choice of conjunctor) and complex structures related to information processing in discourse (including: front-weight- structure and thematic structure with changes of Theme element). Problems related to grammar may be solved with language economy and accuracy while those related to discourse may be solved with understanding information packaging patterns in the target language discourse. Keywords: scientific language, complex structures, translation